MICROSATELLITE MARKERS BASED ASSESSMENT OF RUST RESISTANCE GENES IN PAKISTANI BREAD WHEAT GENOTYPES - N. Akhtar1; A. Kiran; Sajid-ur-Rehman; M. Kausar; M. Khan; U. Saleem; T. Mahmood (Journal of Animal and Plant Sciences, 2020)
Development of rust resistant wheat cultivars to meet ever-increasing wheat production targets for national food security in climate change scenario is currently at high priority in Pakistan. Focusing on this, here we report the screening of 40 wheat genotypes including advanced breeding lines and commercial varieties through PCR based DNA markers to detect genes conferring resistance against different rust races. In this study 22 SSR/STS markers were used which included nine leaf rust (Lr19, Lr22a, Lr27, Lr28, Lr34, Lr35, Lr37, Lr46 and Lr67), eight stripe rust (Yr5, Yr15, Yr17, Yr18, Yr26, Yr29, Yr30 and Yr46) and seven stem rust resistance genes (Sr2, Sr22, Sr24, Sr25, Sr26, Sr38 and Sr39). The results revealed that allelic frequency for rust resistance genes (Lr, Yr and Sr) was maximum (70.4%) in three advanced wheat lines namely V-9452, V-11153 and NNG-3. However, minimum frequency (51.9%) was found in 25 genotypes. Three advanced lines NNG-3, V-9432 and V-11153 had maximum number of rust resistance genes among all the reported wheat genotypes which indicated narrow genetic base of Pakistani wheat cultivars for rust resistance. Therefore, it is suggested that newly discovered rust resistance genes especially Lr and Yr should be used along with existing genes for effective and durable rust resistance in new wheat varieties.
Keywords: Gene; heat map; DNA markers; PCR; SSR